Selection and validation of stable reference genes for RT-qPCR analysis across seven Musa genomes during early flowering development - KAWEE SUJIPULI; YONLADA MINGMANIT; PHITHAK INTHIMA; SRISANGWAN LAYWISADKUL; KUMROP RATANASUT; DUANGPORN PREMJET; SIRIPONG PREMJET; PONGSANAT PONGCHAROEN; WANWARANG PATHAICHINDACHOTE; MAHATTANEE PHINYO; THANITA BOONSRANGSOM (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Sujipuli K, Mingmanit Y, Inthima P, Laywisadkul S, Ratanasut K, Premjet D, Premjet S, Pongcharoen P, Pathaichindachote W, Phinyo M, Boonsrangsom T. 2025. Biodiversitas 26: 125-135. Banana (Musa spp.) is a globally important fruit crop, with most edible varieties resulting from hybridizations between Musa acuminata (AA genome) and Musa balbisiana (BB genome). Seed formation in hybrid bananas is undesirable for both fresh consumption and processing, making it crucial to understand the genetic mechanisms controlling pollen viability and development to prevent seed set in commercial cultivation. However, comprehensive evaluations of reference genes for gene expression studies in various Musa genomic groups are still lacking. This study evaluated five candidate reference genes-ACT2, CAC, RPS4, RPL4, and SAMDC1-across seven Musa genomes using reverse transcriptase quantitative real-time PCR (RT-qPCR). Four of these genes (CAC, RPS4, RPL4, and SAMDC1) demonstrated high primer specificity, with single PCR amplification peaks and melting curve Tm values ranging from 75.42 ± 0.03 to 82.51 ± 0.03. Expression abundance varied, with Ct values between 21.58 ± 0.26 and 24.68 ± 0.20. Using five stability analysis programs, CAC was identified as the most stable reference gene across all seven Musa genomes, making it the optimal candidate for normalizing gene expression data in banana studies. This study provides a valuable tool for enhancing the accuracy of gene expression analysis in banana breeding programs targeting seedless fruit production, thereby demonstrating the practical relevance of reference gene evaluation in banana genomic studies.